Robustness of Tomato Quality Evaluation Using a Portable Vis-SWNIRS for Dry Matter and Colour - U. K. Acharya; P. P. Subedi; K. B. Walsh (International Journal of Analytical Chemistry)
The utility of a handheld visible-short wave near infrared spectrophotometer utilising an interactance optical geometry was assessed in context of the noninvasive determination of intact tomato dry matter content, as an index of final ripe soluble solids content, and colouration, as an index of maturation to guide a decision to harvest. Partial least squares regression model robustness was demonstrated through the use of populations of different harvest dates or growing conditions for calibration and prediction. Dry matter predictions of independent populations of fruit achieved R2 ranging from 0.86 to 0.92 and bias from −0.14 to 0.03%. For a CIE a⁎ colour model, prediction R2 ranged from 0.85 to 0.96 and bias from −1.18 to −0.08. Updating the calibration model with new samples to extend range in the attribute of interest and in sample matrix is key to better prediction performance. The handheld spectrometry system is recommended for practical implementation in tomato cultivation.